Full field optical measurements in experimental modal analysis and model updating. (3rd March 2019) - Zanarini, Alessandro
Abstract: We might doubt if optical measurements and spatially dense datasets are really effective, when dealing with advanced model updating of lightweight structures with complex structural dynamics. Laser Doppler Velocimetry, with its scanning variances, is generally accepted as the reference technology in measuring vibration patterns with high spatial definition. Nonetheless, one must be reminded of the noise shown in the raw signal of some experiments, which poses issues in proficiently exploiting the added data in a fruitful model updating procedure. Instead, native full field measuring technologies, like Hi-Speed DIC and dynamic ESPI, have recently shown intrinsic smoother data fields: their image-based nature and evaluation algorithms of experimental quantities promise advances on model optimisations, having to struggle less against a reduced uncertainty in the references. In this work, a comparison is made by means of all the cited challenging technologies on the same broad frequency band vibration measurement problem, with different spatial resolutions and quality of the measured patterns, in the framework of established procedures for model updating of dynamically excited structures. The identification of EMA models highlights the increasing quality of shapes that can be obtained from native full field high resolution instruments, against that of SLDV (some time unexpectedly poor, as tested). A comparative paradigm is recalled to precisely match the competing measurement technologies on the same physical point of a common grid: model updating results are therefore thoroughly compared between scanning and native full field technologies, with comments and details on the test rig, on the advantages and drawbacks of the approaches. The model updating procedures show a fruitful impact of the native full field technologies in the form of an increased consistency on eigenshapes used to tune the virtual structural model.